DAMPAK FRAMING EFFECT DAN SELF EFFICACY DALAM PENGAMBILAN KEPUTUSAN INVESTASI (ANALISIS PROGRAM “MINI GOLD: SEMUA BISA PUNYA EMAS”) - Arovia Devi Cahyanti; Arisyahidin Arisyahidin; Abu Talkah (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Investment decision making is inseparable from human behavior that allows for irrational behavior. The purpose of this study was to determine the effect of framing effect and self-efficacy on housewives' investment decisions. This study uses a quantitative approach. Methods of data collection using questionnaires and literature study. The populations in this study are housewives who live in the city of Kediri. Samples were taken as many as 50 respondents with special criteria, namely having investment experience. The research instrument test uses validity and reliability tests. The analysis prerequisite test used normality test, heteroscedasticity test and multicollinearity test. The data analysis technique used simple linear regression analysis. The results of this study the framing effect variable has a significant influence on the investment decisions of housewives in Kediri City. Each change in the framing effect variable has an effect of 45.6% which has a real and positive effect on changes in the investment decision variable. This is in line with the theory that the Framing Effect consistently proves to be one of the biggest biases in decision making. The self-efficacy variable has a significant influence on the investment decisions of housewives in Kediri City. Each change in the self-efficacy variable has an effect of 77.4% which has a real and positive effect on changes in the investment decision variable. This is in accordance with the theory of financial self-efficacy, namely individuals who have a higher sense of self-control can solve financial problems or with a view of "problems to be solved, rather than threats to be avoided".